2018
DOI: 10.3758/s13415-018-0642-0
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and joint action in Parkinson’s disease

Abstract: It has been suggested that the Theory of Mind (ToM) may rely on more basic processes of social cognition, such as action control (e.g., joint action), even if little is known about this relationship. The relationship between ToM and joint action can be studied in patients with Parkinson's disease (PD), because they are characterized not only by a deficit in ToM (and in its cognitive and affective subcomponents) but also by a deficit in the inhibition of competing responses. Sixty PD patients and 60 matched hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Indeed, females are expected to be friendlier and more communal than males in society (e.g., Eagly and Wood, 1999;Witt and Wood, 2010). Thus, the Sex effect on JFE could be related not only to the gender differences in processing irrelevant stimuli such as flankers, but also to gender differences in inhibiting the social processing, given that in the joint Eriksen task the co-actor was an attention-grabbing event which impaired females' ability to focus their selective attention on the central target (Dittrich et al, 2017;Fabbri et al, 2018b). Although previous arguments seemed to be speculative, the lack of significant comparisons between JFE or SFE and standard FE (with the sole exception of SFE in females) showed that the materials used in all tasks were reliable, given that the stimuli induced and exerted similar response-related processing with similar flanker effects between conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, females are expected to be friendlier and more communal than males in society (e.g., Eagly and Wood, 1999;Witt and Wood, 2010). Thus, the Sex effect on JFE could be related not only to the gender differences in processing irrelevant stimuli such as flankers, but also to gender differences in inhibiting the social processing, given that in the joint Eriksen task the co-actor was an attention-grabbing event which impaired females' ability to focus their selective attention on the central target (Dittrich et al, 2017;Fabbri et al, 2018b). Although previous arguments seemed to be speculative, the lack of significant comparisons between JFE or SFE and standard FE (with the sole exception of SFE in females) showed that the materials used in all tasks were reliable, given that the stimuli induced and exerted similar response-related processing with similar flanker effects between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should address in deep way which account in a better way explains the joint action effects. Finally, the go/no-go joint paradigms are a valuable educational or rehabilitative tool (Fabbri et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation